DECOLONIZING SOUTH AFRICAN SOCIOLOGY: Building on a Shared "Text of Blackness". (13th May 2016) - Mangcu, Xolela
Abstract: On 14 June 2014 the Council of the University of Cape Town (UCT) voted to change race-based affirmative action in student admissions. The Council was ratifying an earlier decision by the predominantly White University Senate. According to the new policy race would be considered as only one among several factors, with the greater emphasis now being economic disadvantage. This paper argues that the new emphasis on economic disadvantage is a reflection of a long-standing tendency among left-liberal White academics to downplay race and privilege economic factors in their analysis of disadvantage in South Africa. The arguments behind the decision were that (1) race is an unscientific concept that takes South Africa back to apartheid-era thinking, and (2) that race should be replaced by class or economic disadvantage. These arguments are based on the assumption that race is a recent product of eighteenth century racism, and therefore an immoral and illegitimate social concept. Drawing on the non-biologistic approaches to race adopted by W. E. B. Du Bois, Tiyo Soga, Pixley ka Seme, S. E. K. Mqhayi, and Steve Biko, this paper argues that awareness of Black perspectives on race as a historical and cultural concept should have led to an appreciation of race as an integral part of people's identities, particularly those of the Black students on campus. Instead of engaging with these Black intellectual traditions, White academics railroaded their decisions through the governing structures. This decision played a part in the emergence of the #RhodesMustFall movement at UCT. This paper argues that South African sociology must place Black perspectives on race at the center of its curriculum. These perspectives have been expressed by Black writers since the emergence of a Black literary culture in the middle of the nineteenth century. These perspectives constitute what Henry Louis Gates, Jr. calls a shared "text of Blackness" (Gates2014, p. 140). This would provide a practical example of the decolonization of the curriculum demanded by students throughout the university system.